Cotton (Gossypium hirsutum) Cultivars Exhibiting Tolerance to the Reniform Nematode (Rotylenchulus reniformis) - Julie A. Blessitt; Salliana R. Stetina; Ted P. Wallace; Peggy T. Smith; Gabriel L. Sciumbato (International Journal of Agronomy)
A field study was conducted over a two-year period (2006-2007) at the Delta Research and Extension Center, Stoneville, MS, USA to screen selected entries in the 2006 Mississippi Cotton Variety Trials for tolerance to the reniform nematode (Rotylenchulus reniformis). Trials were conducted in nonirrigated fields with primarily sandy loam soils. Though some variability was noted between test locations and years, six of 13 cotton (Gossypium hirsutum) cultivars tested were considered tolerant to the reniform nematode: “Cropland Genetics 3520 B2RF,” “DynaGrow 2520 B2RF,” “Stoneville 5242 BR,” “Stoneville 5599 BR,” “Deltapine 488 BG/RR,” and “Fibermax 960 B2R.” Of these, the first three exhibited yields similar to the productive cultivar “Deltapine 445 BG/RR” in all environments. Though they will not suppress the reniform nematode population, these cultivars can help reduce economic losses attributed to this pathogen in the Midsouth region of the USA.